2018
DOI: 10.3892/or.2018.6680
|View full text |Cite
|
Sign up to set email alerts
|

Increasing HER2 α2,6 sialylation facilitates gastric cancer progression and resistance via the Akt and ERK pathways

Abstract: Upregulated β-galactoside α2,6-sialyltransferase I (ST6Gal-I) expression reportedly occurs in many cancers and is correlated with metastasis and poor prognosis. However, the mechanisms by which ST6Gal‑I facilitates gastric cancer progression remain poorly understood. Trastuzumab is exclusively used in human epidermal growth factor receptor 2 (HER2)+ gastric cancers; however, most advanced HER2+ gastric cancers develop trastuzumab resistance. Herein, we identified HER2 as an ST6Gal‑I substrate and showed that H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…α2,6-sialylation in hepatocellular carcinoma activated Wnt/β-catenin signaling to promote tumor cell proliferation, migration, and invasion [62]. Increased α2,6-sialylation on the human epidermal growth factor receptor 2 (HER2) facilitated gastric cancer progression via the Akt and ERK pathways [63]. Sialylation on the endothelial growth factors receptor (EGFR) was regulated by ST6GAL1 via the PI3K/Akt pathway [64], and inhibition of ST6GAL1 induced EGFR desialylation and anti-proliferation [65].…”
Section: Sialic Acids Enhance Tumor Proliferation and Metastasismentioning
confidence: 99%
“…α2,6-sialylation in hepatocellular carcinoma activated Wnt/β-catenin signaling to promote tumor cell proliferation, migration, and invasion [62]. Increased α2,6-sialylation on the human epidermal growth factor receptor 2 (HER2) facilitated gastric cancer progression via the Akt and ERK pathways [63]. Sialylation on the endothelial growth factors receptor (EGFR) was regulated by ST6GAL1 via the PI3K/Akt pathway [64], and inhibition of ST6GAL1 induced EGFR desialylation and anti-proliferation [65].…”
Section: Sialic Acids Enhance Tumor Proliferation and Metastasismentioning
confidence: 99%
“…N-acetylneuraminic acid (Neu5Ac) and N-glycolylneuraminic acid (Neu5Gc) are the two major sialic acids in mammals [3]. Because of their negative electric charge, sialic acids play crucial roles in a variety of cellular functions, e.g., cell-cell interaction, determining conformation of glycoproteins on cell membranes, and masking antigenic determinants on receptor molecules [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…High expression of ST6Gal-I is correlated with decreased overall and progression free survival in patients with high-grade serous ovarian carcinoma [9,10], the most common and aggressive subtype [1]. ST6Gal-I regulates tumor cell phenotype by modulating the sialylation, and therefore function, of key receptors that drive malignant cell behaviors [11][12][13][14][15][16][17]. We and others have shown that ST6Gal-I activity confers all of the hallmark features of a CSC including increased expression of canonical CSC markers [18], invasive potential [16,19], tumor-initiating potential [9,20], and resistance to hypoxia, chemotherapeutics, and radiation [14,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%